Effect of hyperoxia during the rest periods of interval training on perceptual recovery and oxygen re-saturation time - Peeling, P.; Andersson, R. (Journal of Sports Sciences, 2011)
The effect of hyperoxic gas supplementation on the recovery time of oxygen saturation levels (SaO2), and its effect on perceptual recovery were assessed. Seven national-level kayak athletes completed two laboratory-based ergometer sessions of 6 × 3-min maximal aerobic intervals, with 2 min recovery between repetitions. During each recovery period, athletes either inhaled a hyperoxic gas (99.5 ± 0.2 % FIO2) or were given no external supplementation (control). Mean power output, stroke rate, heart rate, and ratings of perceived exertion were collected during each interval repetition, and the intensity was matched between trials. During each 2-min recovery period, post-exercise haemoglobin saturation levels were measured via pulse oximetry (SpO2), and the time taken for the SpO2 to return to pre-exercise values was recorded. Subsequently, a rating of perceived recovery quality was collected. There were no differences in the levels of post-exercise de-saturation between the hyperoxic and control trials (P < 0.05), although the recovery time of SpO2 was significantly faster in the hyperoxic trial (P < 0.05). There was no influence of oxygen supplementation on the athletes' perception of recovery quality. Hyperoxic gas supplementation during the recovery periods between high-intensity intervals substantially improves the recovery time of SpO2 with no likely influence on recovery perception.